Segmentasi Pelanggan berdasarkan RFM sebagai Dasar Strategi Pemasaran Studi Kasus di PT Five Ocean Indonesia terhadap Permintaan Tenaga Kerja Maritim - Bachrie Harahap, Ahmad Ilham; Ganang Kartiko Aji; Mufti Kusuma Firdaus; Jerry Heikal (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze PT Five Ocean Indonesia's partner segmentation in meeting maritime workforce needs as a basis for developing data-driven marketing strategies. The research method used a quantitative approach using the RFM (Recency, Frequency, Monetary) technique and data processing using SPSS. The results indicate that the company's partners can be categorized into three main segments: Best Customers, Potential Customers, and Potential Customers, based on their RFM scores. Most partners fall into the medium transaction value and medium request frequency categories, while only a small percentage consistently contribute high volumes. The study concludes that the RFM method is effective in identifying partner behavior and supporting the company in designing retention, reactivation, and market development strategies to increase competitiveness and business desirability in the maritime workforce industry.   Keywords: Partner Segmentation, Maritime Workforce, Data-Driven Marketing Strategy